2018
DOI: 10.4049/jimmunol.1700229
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Macrophages in the Response to TNF Inhibition in Experimental Arthritis

Abstract: The reduction of synovial tissue macrophages is a reliable biomarker for clinical improvement in patients with rheumatoid arthritis (RA), and macrophages are reduced in synovial tissue shortly after initiation of TNF inhibitors. The mechanism for this initial response is unclear. These studies were performed to identify the mechanisms responsible for the initial reduction of macrophages following TNF inhibition, positing that efflux to draining lymph nodes was involved. RA synovial tissue and synovial fluid ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…We have recently found that there is a requirement for GM-CSF in the same exogenous TNFdriven model (40), again indicating a link between the activities of the two CSFs in question. It has been proposed that the successful treatment of the TNF transgenic mouse arthritis model with a TNF inhibitor was due to decreased migration of monocytes and/or increased synovial macrophage apoptosis (64); based on our finding, perhaps CSF-1 could be involved in regulating these functions. Also, and encouragingly for any clinical applications arising from our above findings, the benefit of early but not late CSF-1 blockade parallels that of anti-TNF blockade for ZIA (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…We have recently found that there is a requirement for GM-CSF in the same exogenous TNFdriven model (40), again indicating a link between the activities of the two CSFs in question. It has been proposed that the successful treatment of the TNF transgenic mouse arthritis model with a TNF inhibitor was due to decreased migration of monocytes and/or increased synovial macrophage apoptosis (64); based on our finding, perhaps CSF-1 could be involved in regulating these functions. Also, and encouragingly for any clinical applications arising from our above findings, the benefit of early but not late CSF-1 blockade parallels that of anti-TNF blockade for ZIA (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Infiltrating synovial macrophages originate from blood monocytes. These macrophages are considered as short lifespan cells constantly recruited in the inflammatory synovium: they experience activation-induced cell death (34, 35), apoptosis induced by therapeutic agents (22, 32, 36), and eventually efflux from synovium (37). We used monocyte-derived macrophages submitted to pro-inflammatory conditioning to model the contribution of these infiltrating macrophages to rheumatoid synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely, both of these macrophage subpopulations also express of F4/80 and CD11b and, thus, can be targeted by MYSTIs in order to retain and inhibit TNF on their cell surface. It was shown that neutralization of TNF may affect the phenotype of monocytes and macrophages both at the systemic level and locally in the inflamed joint . Identification of individual cellular molecular markers could contribute to the development of new therapeutic approaches for targeting pathogenic cells involved in inflammation, while maintaining the functional activity of anti‐inflammatory macrophages in RA.…”
Section: Resultsmentioning
confidence: 99%